Cross-kingdom regulation of gene expression in giant pandas via plant-derived miRNA - Tan, Helin; Wang, Chengdong; Li, Feng; Peng, Yue; Sima, Jiacheng; Li, Ying; Deng, Linhua; Wu, Kai; Xu, Zhongxian; Zhang, Zejun (Frontiers in Veterinary Science, 2025)
Giant pandas (Ailuropoda melanoleuca) belong to the order Carnivora, but they mainly feed on bamboo, and their unique dietary adaptability has always been the focus of research. Recent research indicates that plant-derived microRNAs (miRNAs) can be delivered to animal organisms via exosomes and exert cross-kingdom regulatory effects on gene expression. To explore the role of plant-derived miRNAs in the dietary adaptation of giant pandas, we collected peripheral blood samples from three groups of pandas: juvenile females, adult females, and adult males—and extracted exosomes from the blood for small RNA sequencing. Additionally, three types of bamboo (shoots, stems, and leaves) consumed by the pandas were sampled for miRNA sequencing. Through comparative analysis, we identified 57 bamboo-derived miRNAs in the extracellular exosomes of giant panda peripheral blood. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses of the target genes for these miRNAs revealed their involvement in various pathways, including taste and olfactory signal transduction, digestion and absorption, and hormonal signal transduction. Furthermore, we found that plant-derived miRNAs can modulate dopamine metabolism in giant pandas, thereby influencing their food preferences. This study shows that plant-derived miRNAs can enter the bloodstream of giant pandas and exert cross-kingdom regulatory effects, potentially playing a vital role in their dietary adaptation process.